2003
DOI: 10.1037/0022-006x.71.4.754
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing in drug abuse services: A randomized trial.

Abstract: Motivational interviewing (MI) is a directive, client-centered brief intervention to elicit behavior change by helping clients explore and resolve ambivalence. In this clinical trial, 152 outpatients and 56 inpatients entering public agencies for treatment of drug problems were randomly assigned to receive or not receive a single session of manual-guided MI. Drug use was assessed by self-report, urine toxicology, and collateral reports from significant others at baseline, 3, 6, 9, and 12 months. Contrary to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(127 citation statements)
references
References 50 publications
9
109
0
5
Order By: Relevance
“…Given that MI was initially developed and validated as an intervention for alcohol use disorders, and that recent studies suggest that MI may be more effective among alcohol, rather than drug-using, populations (Miller et al, 2003), additional exploratory analyses were conducted to evaluate outcomes for the large subpopulation whose principal substance used was alcohol (n = 177). For this subgroup, those assigned to MI completed significantly more sessions in the 28 days following randomization compared with those assigned to the standard evaluation session (MI mean = 5.1 sessions (S.D.…”
Section: Subgroup Analyses: Alcohol Usersmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that MI was initially developed and validated as an intervention for alcohol use disorders, and that recent studies suggest that MI may be more effective among alcohol, rather than drug-using, populations (Miller et al, 2003), additional exploratory analyses were conducted to evaluate outcomes for the large subpopulation whose principal substance used was alcohol (n = 177). For this subgroup, those assigned to MI completed significantly more sessions in the 28 days following randomization compared with those assigned to the standard evaluation session (MI mean = 5.1 sessions (S.D.…”
Section: Subgroup Analyses: Alcohol Usersmentioning
confidence: 99%
“…First, although the bulk of studies evaluating MI with drug-using populations have suggested that MI is more effective than no treatment or comparison approaches (Burke et al, 2003;Dunn et al, 2001), several well-conducted studies evaluating MI with comparatively large samples of drug-using individuals have yielded few significant differences between MI and standard care comparison conditions (Miller et al, 2003;Donovan et al, 2001). Second, because the bulk of studies evaluating MI with drug users have evaluated the efficacy of adding an additional MI session to standard treatment, there are relatively few data on the effectiveness of MI under the conditions in which it is most likely to be applied in clinical practice, that is, integrating MI techniques into standard treatment approaches (Dunn et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El planteamiento que formulan permite identificar diferentes niveles de predisposición (estadios de cambio) que puede mostrar una persona cuando se plantea modificar su conducta adictiva (DiClemente, Prochaska, Fairhurst, Velicer, Velásquez y Rossi, 1991;Miller, Yahne y Tonigan, 2003;Prochaska y DiClemente, 1992;Prochaska y Norcross, 2007). El nivel motivacional inferior se corresponde con el estadio en el cual no se tiene conciencia del problema y, por tanto, ninguna intención de modificar la conducta adictiva.…”
Section: Introductionunclassified
“…A EM tem se mostrado aplicável e efetiva (Dunn, Deroo & Rivara, 2001;Miller et al, 2003) em diversos comportamentos e na mudança dos estágios motivacionais (Heather, Rollnick, Bell & Richmond, 1995), na aderência ao processo terapêutico (Daley & Zuckoff, 1998;Lincourt, Kuettel & Bombardier, 2002), na adesão a dietas (Berg-Smith et al, 1999), na redução do uso de álcool (Borsari & Carey, 2000;Monti et al, 1999;Oliveira, 2001;Project Match Research Group, 1997), na redução do uso de maconha (Stephens, Roffman & Curtin, 2000;Stephens, Roffman, Fearer, Williams & Picciano, 2004), na redução do uso de cocaína (Donavan, Rosegren, Downey, Cox & Sloan, 2001), na redução do uso de anfetaminas (Baker, Boggs & Lewin, 2001), na cessação do uso de tabaco (Brown et al, 2003;Butler et al, 1999;Colby, 1998;Rodriguez, 2003;WHO 1996) e em pacientes com diabetes (Burke et al, 2002;Channon, Smith & Gregory, 2003). Comparada com o não-tratamento e com o uso de placebo, a EM foi superior em comportamentos envolvendo álcool, drogas, dietas e exercícios (Burke et al, 2003).…”
unclassified